2003
DOI: 10.1128/jcm.41.4.1623-1636.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Encapsulated and Noncapsulated Haemophilus influenzae and Determination of Phylogenetic Relationships by Multilocus Sequence Typing

Abstract: A multilocus sequence typing (MLST) scheme has been developed for the unambiguous characterization of encapsulated and noncapsulated Haemophilus influenzae isolates. The sequences of internal fragments of seven housekeeping genes were determined for 131 isolates, comprising a diverse set of 104 serotype a, b, c, d, e, and f isolates and 27 noncapsulated isolates. Many of the encapsulated isolates had previously been characterized by multilocus enzyme electrophoresis (MLEE), and the validity of the MLST scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
305
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(328 citation statements)
references
References 41 publications
19
305
1
Order By: Relevance
“…We also explored the possibility that strains expressing a b-lactamase enzyme (which confers penicillin resistance) might cluster phylogenetically, and found they did not. Previously, a study by Meats et al (2003) has shown phylogenetic diversity between all the strains of H. influenzae using the MLST approach. Our results are consistent with the observations of Erwin et al (2008), who showed considerable diversity within NTHi strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also explored the possibility that strains expressing a b-lactamase enzyme (which confers penicillin resistance) might cluster phylogenetically, and found they did not. Previously, a study by Meats et al (2003) has shown phylogenetic diversity between all the strains of H. influenzae using the MLST approach. Our results are consistent with the observations of Erwin et al (2008), who showed considerable diversity within NTHi strains.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial genomic DNA was extracted from pure cultures of NTHi isolated from NP, TS or MEF samples (if children had AOM). The internal fragments of seven housekeeping genes of NTHi were amplified by PCR, using a PCR Master Mix (Promega) as described previously (Meats et al, 2003). The PCR products were purified using the ExoSAP kit (USB) and identified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for this is that a single genetic event resulting in a new allele can occur by a point mutation, altering only a single nucleotide site, or by a recombinational replacement that will often result in the modification of multiple sites. This typing scheme has been applied successfully to a wide variety of bacterial pathogens such as Staphylococcus aureus [14], Campylobacter jejuni [12], and Haemophilus influenzae [26], to cite only a few. This approach has multiple applications such as phylogeny [18], molecular structure analysis [42], and molecular epidemiology.…”
Section: Epidemiological Analysismentioning
confidence: 99%
“…Therefore, MLST databases for a number of different species were searched for high-D SNP sets. Species subject to this analysis were Burkholderia pseudomallei/ Burkholderia mallei, Helicobacter pylori, Campylobacter jejuni, Streptococcus pneumoniae, Streptococcus pyogenes and Enterococcus faecium (Feil et al, 2000;Enright et al, 2001;Sa-Leao et al, 2001;Dingle et al, 2002;Homan et al, 2002;Godoy et al, 2003;Meats et al, 2003). Ten different sets of SNPs were identified for each species.…”
Section: Identification Of High-d Snp Sets In Other Organisms and Commentioning
confidence: 99%